Sexual Harassment in Academia Ethical Climates and Bounded Ethicality. [article]. - Tenbrunsel, Ann E.
For more than 50 years, psychologists, gerontologists, and, more recently, neuroscientists have considered the possibility of successful aging. How to define successful aging remains debated, but well-preserved age-sensitive cognitive functions, like episodic memory, is an often-suggested criterion. Evidence for successful memory aging comes from cross-sectional and longitudinal studies showing that some older individuals display high and stable levels of performance. Successful memory aging may be accomplished via multiple paths. One path is through brain maintenance, or relative lack of age-related brain pathology. Through another path, successful memory aging can be accomplished despite brain pathology by means of efficient compensatory and strategic processes. Genetic, epigenetic, and lifestyle factors influence memory aging via both paths. Some of these factors can be promoted throughout the life course, which, at the individual as well as the societal level, can positively impact successful memory aging. -- (from the author)
Keywords: McKenzie, Rees R; Sexual harrassment; Ethical climate; Bounded ethicality; Ethical fading; Motivated blindness; Slippery slope